Dangerous deception - Garcia, Kami (Garcia, Kami. Dangerous creatures., 2015)
Some loves are cursed. Others are dangerous. Especially the love between wannabe rocker and quarter Incubus, Wesley 'Link' Lincoln, and Dark Caster, Siren, and bona fide bad girl, Ridley Duchannes. But now Ridley is missing, and Link was with her, right up until she vanished. Determined to find her, Link reunites with his New York bandmates and the mysterious Lennox Gates, who wants Rid for himself.